Implementasi Pendekatan Manajemen Berbasis Sekolah: Profil Sekolah Dasar di Wilayah Desa Tertinggal - Punaji Setyosari (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
The Implementation of School-Based Management Approach: Profile of Elementary Schools in the Underdeveloped Villages. The purpose of the study were to describe the general conditions of the school system, the input factors existing at the school, the factors or supporting conditions upon the school, the school atmosphere, the implementation of teaching-learning process, and things had been achieved by the school. Questionnaires and observation guides were used to collect the data. The research results showed that the school condition was generally good, most of the students (90%) were disadvantaged, parental or societal participation upon education was low, school autonomy and teacher commitment were low, and the students’ achievement as indicated in the scores of the national examination were not satisfactory.